The Impact of Digitalization on Customer Satisfaction in Nepalese Commercial Banks. - Niroula, Ballav (Jurnal Studi Manajemen dan Bisnis, 2024)
This study aims to analyze the impact of digitalization on customer satisfaction in Nepalese Commercial Banks. The study assesses how each of these variables affects customers' perceptions and satisfaction levels with banking digitalization services. The main objectives of this study are to evaluate the relationship between digital adoptions, mobile engagement, technical infrastructure, and user experience on customer satisfaction, and to analyze the impact of digitalization on customer satisfaction in the context of Nepalese Commercial Banks. The clients of 20 commercial banks are the total population of this study. However, a total of 365 questionnaires were distributed among them only 320 questionnaires were acquired which were sent through Google Forms, and some questionnaires were distributed to the clients of the commercial banks. The research adopts quantitative research as a descriptive and causal-comparative research design, convenience and purposive sampling were used for data collection for a Five-point Likert scale. Data analysis tools included descriptive, correlation, and coefficient of variation. The digital adaptation has the highest mean score, which means digital banking services have made it easier for customers to manage their accounts, and Customers are least satisfied due to mobile engagement. And the customers do not feel secure while using the mobile apps for transactions. As per the correlation, all the variables have a positive correlation with customer satisfaction. Among them, Technical Infrastructure has highly positively correlated and least correlated with Mobile Engagement As per the regression analysis all the variables have a positive impact of digitalization on customer satisfaction since they have a p-value (0.000) which is less than 0.05 level.